Penyuluhan Hukum Anti Korupsi di Lingkungan SMA Muhammadiyah 1 Pontianak - Anshari Anshari; Heru Yudi Kurniawan (Universitas Muhammadiyah Pontianak, 2018)
Corruption in Indonesia is growing very rapidly, corruption is widespread everywhere and happens systematically. Often corruption is done with sophisticated engineering and utilizing modern technology. The prevention and prevention of corruption can take the form of various kinds, one of which is to instill an anti-corruption culture through anti-corruption counseling in adolescents, youth, and / or students in school. In order to improve the nation's morals, the strengthening of aspects through an anti-corruption culture from an early age is a crucial task for the academic community as a form of community service, nation and state. Through anti-corruption counseling in schools (in this case Muhammadiyah 1 Pontianak High School), it is expected that the younger generation (students or students) are able to absorb the material from the anti-corruption education. This is done to increase students' knowledge about what factors a person commits corruption, about prohibitions and criminal threats against someone who commits corruption, behavior, morality and morals of a person in life in society.